2012
DOI: 10.1021/jp306765b
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of the Binding of Silane (SiH4) with Borane (BH3), Diborane (B2H6), and Boron Trichloride (BCl3): The Role of Core–Electron Correlation

Abstract: Equilibrium structures and energies of gas-phase molecular complexes SiH(4)···BH(3), SiH(4)···B(2)H(6), and SiH(4)···BCl(3) were determined using second-order Møller-Plesset perturbation theory (MP2) and the aug-cc-pVTZ basis set, with and without explicit core electron correlation. Single-point energies were calculated for the MP2-optimized structures using MP2 with the aug-cc-pVQZ basis set and using coupled cluster theory (CCSD(T)) with both the aug-cc-pVTZ and the aug-cc-pVQZ basis sets to extrapolate to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
0
5
1
Order By: Relevance
“…Intriguingly, theoretical studies by Kim and Gordon suggested that Lewis acid BH 3 could form Type II σ-complexes with SiH 4 in gas phase in which one of the H–Si bond is substantially activated. Recently Piers successfully isolated a borane-HSiEt 3 adduct with a borole derivative, 1,2,3-tris­(pentafluorophenyl)-4,5,6,7-tertafluoro-1-boraindene .…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, theoretical studies by Kim and Gordon suggested that Lewis acid BH 3 could form Type II σ-complexes with SiH 4 in gas phase in which one of the H–Si bond is substantially activated. Recently Piers successfully isolated a borane-HSiEt 3 adduct with a borole derivative, 1,2,3-tris­(pentafluorophenyl)-4,5,6,7-tertafluoro-1-boraindene .…”
Section: Introductionmentioning
confidence: 99%
“…For comparison, a-cc-pVTZ single point energies are also computed. Results and literature values are collected in Table .…”
Section: Results and Discussionmentioning
confidence: 99%
“… a Shorter Si–B bond. b Based on MP2­(AE*)/a-cc-pwCVTZ geometry. c Taken from ref , AE* results corresponds to the partial frozen-core treatment. …”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations